The Role of Transient Receptor Potential (TRP) Channels in the Transduction of Dental Pain - Hossain, Mohammad Zakir; Bakri, Marina Mohd; Yahya, Farhana; Ando, Hiroshi; Unno, Shumpei; Kitagawa, Junichi (MDPI, 2019)
Dental pain is a common health problem that negatively impacts the activities of daily living. Dentine hypersensitivity and pulpitis-associated pain are among the most common types of dental pain. Patients with these conditions feel pain upon exposure of the affected tooth to various external stimuli. However, the molecular mechanisms underlying dental pain, especially the transduction of external stimuli to electrical signals in the nerve, remain unclear. Numerous ion channels and receptors localized in the dental primary afferent neurons (DPAs) and odontoblasts have been implicated in the transduction of dental pain, and functional expression of various polymodal transient receptor potential (TRP) channels has been detected in DPAs and odontoblasts. External stimuli-induced dentinal tubular fluid movement can activate TRP channels on DPAs and odontoblasts. The odontoblasts can in turn activate the DPAs by paracrine signaling through ATP and glutamate release. In pulpitis, inflammatory mediators may sensitize the DPAs. They could also induce post-translational modifications of TRP channels, increase trafficking of these channels to nerve terminals, and increase the sensitivity of these channels to stimuli. Additionally, in caries-induced pulpitis, bacterial products can directly activate TRP channels on DPAs. In this review, we provide an overview of the TRP channels expressed in the various tooth structures, and we discuss their involvement in the development of dental pain.